Nutritional intervention in track and field athletes - Sillero Quintana, M.; Garcia Aparicio, A.; Torres Garcia, A.; Garrido Pastor, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Optimal nutrition contributes to achieve maximum athletic performance. Track and field events include the development of different motor skills: race walking, running, jumping, and throwing. The aim of this work is to compare nutritional patterns in athletes competing in different events, and verify possible changes in dietary practices after intervention. Methods Diet composition was analysed in 44 Spanish elite athletes [26 female (F) and 18 male (M)] competing in three different events: fast events (FE) include jumpers, throwers, and multi-event (n = 12; Age =22.5 ± 4.8; BMI = 22.4 ± 3.9), middle distance (MD) runners (n = 17; Age =24.7 ± 4.0; BMI = 20.0 ± 1.5) and long distance (LD) runners (n = 15; Age =24.9 ± 4.9; BMI = 19.4 ± 1.1), to describe and compare their usual nutritional patterns. After a preliminary diet evaluation, an individual nutritional report was given and a personal advice program was performed to all of them focusing on improving their diet quality. To verify possible changes after this intervention, a new diet composition evaluation was done (160 ± 88 days after) in 27 of them (8 FE, 11 MD and 9 LD). Diet composition was estimated by retrospective method for a 3 day period (rest, moderate, and intense training days); additionally, they completed a 24h activity questionnaire to estimate energy requirements (EER) (IOM, 2002) during the same 3 day period. Results Comparing data between the three groups (FE, MD and LD): energy intake (EI) and energy distribution (%P, %CH, %L) were similar despite a tendency to a higher %CH and a lower %L in the LD group (FE = EI: 2653± 950, %P: 19, %CH: 46, %L: 35%; MD = EI: 2668 ± 676, P: 17%, ,CH: 45%, L: 35%; LD = EI: 2737 ± 518, P: 16%, ,CH: 51%, L: 32%). EER were similar to IE in the three groups. Attending to gender, absolute values for EI (Kcal/day), P, L and CH (g/day) were significantly lower in females, but these same values, expressed in terms of body weight, were similar in both genders. After intervention, the EER was lower (2516 ± 480 vs 2816 ± 461 kcal/d), and so was the EI (p<0.005) expressed in absolute values (2466 ± 546 vs 2781 ± 763 kcal/d) and relative to body weight (45 ± 12 vs 40 ± 10 Kcal/Kg/d). Elite athletes were able to get an energy balance in both trials. After intervention, CH expressed as % of the total EI was significantly higher (51 ± 8 vs 47 ± 6) (p=0.01), conversely a decreased L intake, expressed as % of the total EI (31 ± 6 vs 36 ± 5), and a significant (p=0.0001) decreased L (saturated and monounsaturated) intake (g/d) were found. Discussion/Conclusion CH intake was still lower than recommended for athletes (Burke, 2007). Other nutritional intervention, such as a personal and close relationship with athletes and their coaches, is needed in order to improve further their diet energy distribution. References IOM. National Academy Press. Washington DC, 2002. Burke L, Maughan R and Shirreff S. J. Sport Sciences, 25 (S1), 2007.